Unsafe spaces?: an ecclesiological evaluation and response to recent controversial practices in some South African neo-Pentecostal churches - Banda, Collium (Verbum et ecclesia, 2020)
From a communal perspective of the church, this article analyses critically the controversial practices reported in some South African neo-Pentecostal (SANP) churches, such as feeding congregants with grass. The article examines the effect of the controversial practices on the meaning of the church. The main question answered in this article is as follows: What is the nature of the church that emerges from the controversial practices reported amongst some SANP churches? And what is a biblically informed understanding of the church that can be used to end these practices that violate the human rights of congregants? The question is answered by describing the controversial SANP practices and examining the theological foundations of these controversial practices. The article argues for the necessity for a sound church doctrine as a way of curbing these controversial practices. This ecclesiology must take seriously the communal nature of the church. The contribution of the article is showing the need for Christians to take personal responsibility to guard against practices that make their churches unsafe spaces. Intradisciplinary and/or interdisciplinary implications: The article combines perspectives from the communal nature of the church, the Trinity and the salvation mission of the church to analyse the state of the church represented by the controversial SANP churches which use questionable practices, such as healing rituals that involve spraying people with insecticides. The study has direct implications on the doctrine of the church, ministerial practices and foundations of the church that make churches safe places for their members.